PENGARUH METFORMIN TERHADAP PENEKANAN EKSPRESI CYCLIN D1, AKTIVASI p53 DAN INDUKSI APOPTOSIS PADA KULTUR SEL HELA - , RATIH DEWI YUDHANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Indonesia is a country with the highest number of cervical cancer in the world.Chemotherapy for cancer is less favorable and often causes serious side effects. Metformin is widely used as antidiabetic agents. Recent studiesfoundthat metformin had the potentialanticancer effect. This study to determine the anticancer effect of metformin on HeLa cell, as an attempt to discover and develop novel therapeutic strategies in the fight against cancer, particularly cervical cancer. Objective : To asses the potential anticancer effect of metfomin on HeLa cell and specifically to determine the metformin activity on cyclin D1suppression, p53 activation and apoptosis induction in HeLa cell cultures. Methods :Cytotoxic test with MTT assay was performed to determine IC50 metformin in HeLa cells. Observationcyclin D1 suppression and p53 activation by metformin were peformed using immunocytochemistry, whereas apoptosis induction test was done by flowcytometry. Results : Metforminhasa tendencyto inhibitproliferationof HeLa cellswithIC50 59,62mM.Metformin30, 60, and120mMsuppressed cyclinD1expression,activated p53and induced apoptosis in HeLa cellsina dose-dependent manner. Conclusion: Metformin has a tendency to inhibitproliferation and induce apoptosis in HeLa cells culture in a dose-dependent manner. This activity of metformin was associated with its ability to suppress cyclin D1 expression and activation of p53.